MODEL OF SUCCESSFUL DIGITAL TRANSFORMATION OF HIGHER EDUCATION INSTITUTIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The significant impact of the recent global health crisis, combined with the possibility of using digital technologies to conduct online learning, represents an unprecedented opportunity to transform higher education on a European and global scale. We are all part of the digital world and the phenomenon of e-learning will be persistently present and further developed. The expectations are to build a sustainable model that will continue to be applied after overcoming all the challenges. The present article explores the theoretical concepts and the main features of the digital transformation of higher education institutions. As a result of the study some of the advantages and disadvantages of the digital learning have been analyzed. The scientific paper describes a model representing the six most important elements that drive the digital transformation process of the higher education institutions and overcome the identified disadvantages.